Writing History in Angevin Naples. - Lee, Charmaine (Italian Studies, 2017)
The arrival of the Angevin dynasty on the throne of the kingdom of Sicily in 1266 introduced the use of French along with the kind of culture preferred at courts in France. The Angevin monarchs seem to have been particularly fond of history, especially ancient history, with Charles I even taking a copy of the historical compilation, the Faits des Romains, with him to Italy. This paper will follow the different historical texts that were produced and/or circulated in the Regno in French and discuss who promoted them and why. It will argue that the passage from ancient history in French to more local history in the Neapolitan vernacular marks a turning point in the ambitions of the Angevins as they abandoned thoughts of Empire, while developing some sense of a national identity in their southern Italian kingdom.